CHALLENGES AND POSSIBLE IMPROVEMENT OF LIVESTOCK SECTOR IN SOUTH SUDAN: REVIEW PAPER - .A.J., Taban; Tijjani, Kabwanga Ismail; Çakır, Ahmet (International Journal of Research -GRANTHAALAYAH, 2018)
South Sudan has agrıculture as one of the main contributors of her economy since the vast majority of the households engage in different agricultural activities. Among which is Livestock and it is mostly done on small scale. Cattle keepers are faced with challenges like political instability, civil conflicts, cattle raiding, Continuous uncontrolled pastoralism and poor record keeping by stakeholder with less or no initiatives from gov’t to combat the above short comings. The above loopholes among others retard the improvement of the livestock sector. This paper however is meant to highlight the most challenges affecting livestock production, and possible suggestions that can be of use for the organization and the improvement of the livestock sectors. Although South Sudan is considered to be one of the highest Cattle keeping country in Africa, this may be just a mirth once the above issues aren’t timely addressed.